2017
DOI: 10.1615/critreveukaryotgeneexpr.2017019386
|View full text |Cite
|
Sign up to set email alerts
|

lep Expression and Its Role in Obesity and Type-2 Diabetes

Abstract: Obesity is metabolic disorder that increases the risk of diabetes, heart disease, and other metabolic syndromes in human beings. One sign of diabetes is increased blood glucose levels in the body. Glucose levels increase due to problems with insulin secretion or insulin resistance. Maturity onset of diabetes of the young is more common in adults and occurs due to insulin resistance. Both diabetes and obesity are major problems that are responsible for the death of millions of individuals every year, worldwide.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 0 publications
1
16
0
2
Order By: Relevance
“…In our validation experiment, the LEPR gene was upregulated in 93% of the cases. This observation is concordant with previous studies, which showed upregulated gene expression of LEPR in this disease [56][57][58][59]. It was also identified as a future disease risk marker for metabolic dysfunction in a Slovakian population with severe environmental chemical exposures [36].…”
Section: Genes Associated With T2dmsupporting
confidence: 92%
“…In our validation experiment, the LEPR gene was upregulated in 93% of the cases. This observation is concordant with previous studies, which showed upregulated gene expression of LEPR in this disease [56][57][58][59]. It was also identified as a future disease risk marker for metabolic dysfunction in a Slovakian population with severe environmental chemical exposures [36].…”
Section: Genes Associated With T2dmsupporting
confidence: 92%
“…Obesity is a frequent concomitant of type 2 diabetes (T2D) [ 2 ]. It has been estimated that no less than 90% of type 2 diabetics are overweight or obese [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from being the energy storage, the adipose tissue is also an important endocrine organ which secretes numerous substances with biological activity, including adipokines [ 4 , 11 , 12 ]. The literature shows that disturbances of adipokine secretion may contribute to peripheral insulin resistance development and/or impairment of production and action of insulin [ 2 , 13 , 14 ]. Pathophysiological relationships between obesity and T2D have not been fully clarified; nonetheless, adipokines (including leptin, adiponectin, resistin, and visfatin) seem to play an important role [ 2 , 14 – 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leptin is 16 kDa peptide produced and secreted by adipose tissue with a multidimensional physiological role (1). For several years, the potential effect of leptin as an appetite suppressor had been discovered that inducing mutations on its coding gene in animal models led to hyperphagia and energy expenditure resulted in obesity (2,3). Later, the appearance of diabetic status and its-related adverse consequences such as diabetic nephropathy in those with mutated gene was also revealed (4,5).…”
Section: Introductionmentioning
confidence: 99%